Resurrection of Ophichthus zophistius (Actinopterygii: Anguilliformes: Ophichthidae), with a revised diagnosis of O. altipennis - Hibino, Yusuke; Mccosker, John E. (Zootaxa, 2020)
Pisoodonophis zophistius Jordan and Snyder 1901 is redescribed as a valid species of Ophichthus Ahl 1789 based on 46 specimens including the holotype. Although this name has been synonymized under Ophichthus altipennis (Kaup 1856), the former can be distinguished from the latter by a relatively acute snout (vs. strongly acute), presence of irregular obscure bars on the body (vs. bars absent), 11–13 predorsal and 61–63 preanal vertebrae (vs. 8–9 and 52–58, respectively) and 10–14 predorsal and 59–64 preanal lateral-line pores (vs. 7–9 and 55–61, respectively), dorsal-fin origin usually above or behind the pectoral-fin insertion (vs. anterior to the insertion), and tail broad and tapered slowly (vs. becoming slender and tapered rapidly). Furthermore, Ophichthys intermedius Regan 1905 and Microdonophis fasciatus Chu, Wu and Jin 1981 are junior synonyms of O. zophistius, and Ophichthus melanochir Bleeker 1864 is that of O. altipennis.